Copper Supplementation in Broiler Diets: Mechanisms of Action and Performance Improvement: Subject Review - Mohammed, Diyar Jaafar; Noaman, H. A. (American Journal of Biodiversity, 2025)
Broiler diet supplementation with copper is an important strategy that improves growth performance, feed utilization, immune response, and health of poultry. As a critical cofactor of vital metalloenzymes responsible for energy metabolism, bone development, and antioxidant defense of broilers growing fast, copper meets the high metabolic requirement of rapidly growing broilers. In this review, several types of copper sources (traditional inorganic forms, nanoparticles, chelated complexes, etc.) are compared, with respect to bioavailability and environmental safety. It also discusses the need to optimize copper dosage for maximizing benefits and minimizing risks of toxicity in relation with currently permitted doses. Moreover, copper’s role in enhancing gut health and protection against pathogens further supports the positive effects of copper on productivity of poultry. This article summarizes the latest scientific evidence and provides practical recommendations for the nutritionist and the producer seeking to maximize the impact of sustainable copper supplementation in today's commercial poultry.